Lifespan development and the brain the perspective of biocultural co-constructivism - Baltes, Paul B. 1939-2006; Reuter-Lorenz, Patricia A. 1958-; Rösler, Frank 1945- (Cambridge University Press, 2006)
The book focuses on the developmental analysis of the brain-culture-environment dynamic and argues that this dynamic is interactive and reciprocal. Brain and culture co-determine each other. As a whole, this book refutes any unidirectional conception of the brain-culture dynamic. Each is influenced by and modifies the other. To capture the ubiquitous reach and significance of the mutually dependent brain-culture system, the metaphor of biocultural co-constructivism is invoked. Distinguished researchers from cognitive neuroscience, cognitive psychology and developmental psychology review the evidence in their respective fields. A special focus of the book is its coverage of the entire human lifespan from infancy to old age